إستدراكات الأئمة على العقيلة والمورد: جمعا ودراسة - خبزي ناجية (Universty Of El-oued جامعة الوادي, 2024)
الملخص: الاستدراك العلمي من الأعمال الجليلة، تعمل على إثراء ونماء وكمال الدراسات بالنظر فيها تصويبا، وتعقيبا، وتداركا، زيادة، أو اختصارا وإجمالا لما طال أو تفرق منها. وكلما كان العمل قيما وكثرت الحاجة إليه كلما كان جديرا بالنظر والتتبع والاستدراك، ومن بين هذه الأعمال منظومتي العقيلة للشاطبي و مورد الظمآن للخراز، فهما عمدتان لكل من ألف بعدهما في رسم المصاحف، وقد اعتنى بهما العلماء عناية كبيرة في كل مكان، وعلى مر الأزمان. فما الاستدراكات على المنظومتين؟ وما أقوال العلماء في الأوجه المستدركة عليهما؟ وما مدى صحتها؟ وما المعمول به في مصاحفنا؟ وما الراجح من ذلك؟ ونظرا للحاجة إلى تحرير المسائل المهمة التي اختلف فيها علماء الرسم وعرضها على الباحثين ومعرفة أوجه الرسم والضبط المعمول بها في المصاحف وغير المعمول بها والمبثوثة في كتب الرسم جاء هذا البحث والذي كان عنوانه: "استدراكات الأئمة على العقيلة والمورد جمعا ودراسة". وقد قسمت البحث إلى أربعة فصول فصل عرفت فيه بالمنظومتين وفصل عرفت فيه بالرسم العثماني والاستدراك، وفصلين لدراسة ما استدركه الإمام السخاوي على العقيلة، والإمامان ابن عاشر والرجراجي على المورد منتهجة في ذلك المنهج الوصفي، والاستقرائي، والتحليلي. وخلصت في نهاية البحث إلى نتائج من أهمها: أن لاختلاف علماء الرسم في أوجه الرسم، واختلافهم في الاستدراك على المنظومتين أسبابا كثيرة منها سعة أوجه الرسم، وكثرتها وتنوعها، وكذلك سعة اطلاع الأئمة - رحمهم الله على أوجه الرسم وتفوقهم في القراءات والرسم العثماني واللغة العربية، وأن هناك أوجها لم نصل لمعرفتها مبثوثة في الكتب المفقودة. Résumé : Scientific emendation is one of great works that works to enrich, grow, and enhance studies by considering them as correcting, commenting, remedying, increasing or summarizing for what was long or dispersed from them. Whenever the work is valuable and the need for it is more, it is worth considering, scrutiny and emendation. Among these works are the two poems, Al-Aqeela by Al-Shatibi, and Mawrid Al-Thamaan by Al-Kharraz, they are the pillars of everyone who wrote the Qur’an after them, and scholars have taken great care of them everywhere, and throughout time . What are the emendations for the two poems? What do scholars say about these emendations? How true are them? What is applied in our printed copies of the Quran? What is more acceptable? Because of the need to write down the important issues on which the scholars of writing the Quran differed; to present them to researchers; to know the modes of writing and control that are applicable in the Quran, not applicable and widespread in books on writing the Quran, I chose this research, the title of which was: “The Imams’ emendations on Al-Aqeela and Al-Mawrid - Collecting and Study -”. I divided the research into four chapters: a chapter in which I introduced the two poems, a chapter in which I introduced the Uthmani writing and emendation, and two chapters to study what Imam Al-Sakhawi emended about Al-Aqila, and the two Imams Ibn Ashir and Al-Rajraji on AlMawrid, adopting the descriptive, inductive, and analytical approach. At the end of the research, I concluded with results, the most important of which are: There are many reasons for the differences of the Quran writing scholars in the modes of writing, and their differences in emendation on the two poems, including: the breadth of the modes of writing, their abundance and diversity, as well as the breadth of knowledge of the imams - may God have mercy on them - on the modes of writing, and their superiority in readings and Uthmani writing. And the Arabic language, and that there are modes that we did not know that spread in the lost books.
أطروحة دكتوراه تخصص التفسير وعلوم القرآن في العلوم الإسلامية
Keywords: مورد الظمآن - منظومة العقيلة – الاستدراكات - رسم المصاحف